Stability of concrete containing blast-furnace slag following exposure to cyclic elevated temperature - Ahmad Iravani (Acta Polytechnica CTU Proceedings, 2022)
Concrete is widely used in constructions such as industrial floors or airducts in steel- and casting industry where it is often exposed to long-term or cyclic elevated temperatures. For these applications, thermal stability of concrete is of vital importance. The strength reduction dueto elevated temperatures depends on the temperature level and concrete composition. In this study, the effects of blast-furnace slag cement (CEM III/A) and basaltic aggregates were investigated at temperatures 250◦C to 700 ◦C in comparison to conventional Portland cement (CEM I) containing quarzitic aggregates. The concretes were cyclically exposed to high temperatures. Special attention was paid to mass loss, residual compressive and residual flexural strength depending on type of cement and aggregate as well as the number of thermal cycles. Mass loss and strength loss increased with increasing maximum temperature level, as expected. It was generally observed that concretes containing CEM III/A displayed significantly higher residual mechanical properties for almost all temperature levels. Concretes containing a combination of CEM III/Awith basaltic aggregates showed significantly higher stability at elevated temperatures compared to other concrete mixtures. It is further shown that apart from the maximum temperature the number of thermal cycles is important for the residual mechanical properties.